Effects of Entrepreneurship Education as an Entrepreneurial Personality Trait Model under Entrepreneurial Intention for the Future in Surabaya - Sienatra, Krismi Budi (Jurnal Entrepreneur dan Entrepreneurship, 2020)
Entrepreneurship is an important sector that can sustain a country’s economic growth. Entrepreneur can be formed from entrepreneurial personality traits which are supported through formal education that emphasizes entrepreneurship. The purpose of this research is to analyze the effect of entrepreneurial personality traits that consist of self efficacy, proactive personality, and locus of control and entrepreneurship education as moderating variable on entrepreneurial intention. The population in this research is business management active students at Surabaya. Accidental sampling technique that is used produces the total sample of 152 people by distributing questionnaires. The research method that is used in this research is multiple linear regression to find out the effect of the independent variables on the dependent variable and determination coefficient analysis to find out the effect of the moderating variable. The results of the multiple linear regression analysis shows that self efficacy, proactive personality, and locus of control affect significantly on entrepreneurial intention. The results of this research also shows that entrepreneurship education is able to moderate self efficacy on entrepreneurial intention.